Palate shape and size and palatal rugae morphology of children with anterior open bite and normal vertical overbite (2023)
Purpose: To determine differences between open bite and normal vertical overbite regarding distribution, size and clinical appearance of palatal rugae, depth and length of the palate, intercanine and intermolar widths and arch perimeter. Methods: A cross-sectional study was performed in 264 superior models were studied with a 3D analysis system. A total of 132 individuals with AOB and 132 individuals with normal vertical overbite were evaluated, chosen from public schools with ages between 8 and 16 years. Palatal anthropometric features were evaluated. Qualitative analysis of palatal rugae was performed, exploring the shape, direction, unification and sensitivity of the palate. The Mann Whitney and Chi Square tests were used for statistical analyses. Results: The average age was 11.37 +/- 2.27 years for normal overbite and 11.87 for anterior open bite, with 54.9% of women. No significant differences were found between subjects with AOB and subjects with normal vertical overbite regarding intermolar or intercanine width. The maxillary length and depth and the height and width of palatal rugae were lower in the AOB group. The most common rugae shapes were curved and wavy, predominating in the horizontal direction with a parallel distribution. Conclusion: Qualitative evaluation demonstrated asymmetry in the shape, direction and unification of rugae in both groups. Most arch measurements were greater in individuals with AOB. © 2018, International Organisation for Forensic Odonto-Stomatology. All rights reserved.